Colloquial Language in Film Reviews - Zelenka, Tomáš (Univerzita Pardubice, 2017)
This bachelor thesis focuses on the use of colloquial English language in written and spoken film reviews. The first part of this paper provides the theoretical insight to the subjects of film reviews, colloquial language, and multi-word verbs. The latter part of this paper aims the attention at the determination and comparison of the frequency, type, and purposes for the usage of multi-word verbs in written and spoken film reviews.
Hovorový jazyk ve filmových recenzích
Keywords: film review; colloquial English; phrasal verbs; prepositional verbs; phrasal-prepositional verbs; filmová recenze; kolokviální angličtina; frázová slovesa; předložková slovesa; frázovo-předložková slovesa